Sosialisasi Layanan Psikologi dan Pentingnya Kesehatan Mental bagi Anggota Komunitas Jalan Bareng Makassar - Alifia Ainun Rizky; Arsianita Nur Fattah; Fitriana; Zulfikar (Insan Kreasi Media, 2025)
This study discusses the importance of mental health with a focus on providing education related to access to psychological services for members of the Jalan Bareng Makassar community. Mental health is an important aspect in realizing comprehensive health. However, in most developing countries, mental health issues have not been prioritized. This has the potential to have a long-term impact and disrupt individual work activities if they do not immediately receive psychological services. This service aims to educate members of the Jalan Bareng Makassar community about the importance of access to psychological services and the impact of an unhealthy mentality in their activities. This activity involved approximately 25 members of the Jalan Bareng Makassar community as participants and one of the Psychologists from the Humind Wellbeing Center as a facilitator, using an interactive discussion method. The results of this activity indicate that a structured and collaborative approach is effective in increasing understanding of the importance of psychological services in maintaining individual mental health and increasing awareness, as well as participant knowledge regarding the importance of early detection and mental health.